A microkelvin magnetic flux noise thermometer - Rothfuß, Daniel Simon; Reiser, Andreas; Fleischmann, Andreas; Enss, Christian (Journal of low temperature physics, 2014)
Due to its non-driven nature, noise thermometry intrinsically is the method of choice when minimal heat input during the temperature measurement is required. Our noise thermometer, experimentally characterized for temperatures between 42 $${{\upmu }}$$μK and 0.8 K, is a magnetic Johnson noise thermometer. The noise source is a cold-worked high purity copper cylinder, 5 mm in diameter and 20 mm long. The magnetic flux fluctuations generated by the electrons’ Brownian motion is measured inductively by two dc-SQUID magnetometers simultaneously. Cross-correlation of the two channels leads to reduction of parasitic noise by more than one order of magnitude which allows for measuring the tiny noise powers at microkelvin temperatures.